Green Economy Dan Halal Economy Kolaborasi Solutif Menjawab Tantangan Ekonomi Global - Hasanah, Hikmatul; Suprianik, Suprianik (Unversitas Islam Madura, 2022)
ABSTRACT The impact of economic activities on the sustainability of the planet earth is currently very concerning, so that a global commitment has emerged to maintain the sustainability of this earth. The commitment is the implementation of a green economy. Along with this commitment, specifically the commitment of a religious teaching also plays an important role in the success of this global commitment, namely the implementation of the halal economy. Literature review is the method in this research to find theories and similarities between the green economy and the halal economy. The result is that these two economic targets have unidirectional goals so that they will support and strengthen each other if they are collaborated into solutions rather than overcoming the impacts and challenges of the global economy. Key words: Green economy, Halal economy